New Technologies in Urology - Dasgupta, Prokar; Fitzpatrick, John M.; Kirby, Roger; Gill, Inderbir S. (New Techniques in Surgery Series,, 2010)
Extensively and thoroughly written, New Technologies in Urology offers a definitive guide to the ever-changing and expanding landscape of available tools, methods and techniques for urological practice. This book's authorship of highly acclaimed experts in the field ensures that the reader enjoys not only a comprehensive but a highly authoritative report on the latest technological developments in urology and their applications. Including coverage of laser prostatectomy, flexible robotics, prostate focal therapy and renal cryo-ablation, New Technologies in Urology brings the reader the very cutting edge of technologies in the urological field. Professor Prokar Dasgupta MSc(Urol) MD FRCS(Urol) FEBU is Chair in Robotic Surgery and Urological Innovation at Guy's Hospital, King's College London, where he pioneered modern robotic urological surgery in the UK. He has also been awarded the prestigious Karl Storz-Harold Hopkins Golden Telescope award by the British Association of Urological Surgeons for his significant and lasting contribution to urology. Professor John Fitzpatrick MD is a Consultant Urologist and Professor of Surgery at the Surgical Professorial Unit, University College Dublin. He is, amongst many other positions, President of the Irish Society Urology and is immediate Past President of the British Association of Urological Surgeons. Professor Roger Kirby MA MD FRCS FEBU is Clinical Director (Prostate Health) and Registered Provider of The Prostate Centre, London, UK. He is an internationally recognised authority on prostate cancer, benign prostatic hyperplasia and erectile dysfunction. Dr Inderbir S. Gill MD MCh is Chairman, Department of Urology and Associate Dean for Clinical Innovation at the Keck School of Medicine, University of Southern California, USA. He is a world-renowned leader in urologic surgery.